(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
Attempts to legalize euthanasia in Spain have been driven by individual cases that revived the debate in society. The most prominent case was that of Ramón Sampedro in 1998. Since 2010, there were regional laws of dignified death that included the right of terminal patients to refuse treatment, receive palliative care, and record these wishes in the document of Prior Instructions. Until, in Spain, Organic Law 3/2021, of March 24, on the regulation of euthanasia, was approved, which entered into force three months later on June 25, 2021. The approval of Organic Law 3/2021 regulating euthanasia in Spain (LORE) means the legalization for the first time in the history of our country of the provision of aid to die. In this paper we highlight the most important and controversial aspects of the Law. Also emphasizing the importance that has acquired the prior realization of the documents of previous instructions in people who are mentally incapacitated or "in fact" that only in this way can request the request for the provision of help to die. We expose the problem of conscientious objection of health professionals directly involved in providing aid to die. The legal consideration of natural death for this type of benefit. Finally, we talk about the evolution of euthanasia cases in Spain in the first year since the entry into force of the Law.